Das Thema der Kosmogonie in litauischen Folklorenarrativen The Creation Theme in Lithuanian Folk Narratives - Laurinkienė, Nijolė (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this article Lithuanian folk narratives describing the creation of the World and its constituents (Earth, celestial bodies, human beings) are analyzed. By their origin and nature these narratives are supposed to be related to the archaic creation myth, although in many cases they are closely intertwined with successive fragments of Christian religion.